A Parallel Multi-channel Lithium Niobate Electro-optic Modulator - YANG Pengyi (Guangtongxin yanjiu)
【Objective】In order to solve the technical problems of large volume, low integration and small bandwidth of electro-optic modulator, a design method of parallel multi-channel thin film Lithium niobate electro-optic modulator is proposed. The design principle of thin film Lithium niobate electro-optic modulator is presented, and the gain and noise figure of microwave optical transmission link are analyzed.【Methods】A simulation model of microwave optical transmission links is established using Lumerical Interconnect optical simulation software. The effects of modulator half wave voltage on link gain and noise figure are then compared and analyzed. Finally, the key parameters of the 40 GHz four channel integrated thin film Lithium niobate electro-optic modulator are tested.【Results】The test results show that the insertion loss, half wave voltage, 3 dB bandwidth and size of the designed four-channel integrated film Lithium niobate electro-optic modulator are 4.5 dB, 3.5 V, 40 GHz and 30 mm×20 mm×10 mm, respectively. The noise figure of microwave optical transmission link using thin-film Lithium niobate modulator is about 30 dB.【Conclusion】The designed four channel integrated film Lithium niobate electro-optic modulator in this paper is superior to the traditional Lithium niobate electro-optic modulator.